DATAR: a new application for Diversity Assessment Tool for agrobiodiversity and resilience - CGIAR Research Program on Water, Land and Ecosystems (2019)
DATAR is being developed by the Platform for Agrobiodiversity Research (PAR) which is hosted by Bioversity and funded by UNEP. It is in development and testing stage, and expected to reach stage 3 in 2020. By the end of 2020 the Backoffice and APP will be available www.agrobiodiversityplatform.org/datar